Transfer Effects on an Unsteady MHD Mixed Convective Flow Past a Vertical Plate with Chemical Reaction - RAJU, R. Srinivasa (Engineering Transactions, 2017)
An attempt is made to study the effects of chemical reaction and combined buoyancy effects on an unsteady MHD mixed convective flow along an infinite vertical porous plate in the presence of hall current. A uniform magnetic field is applied in a direction normal to the porous plate. The governing coupled non-linear partial differential equations are solved using an efficient Galerkin finite element method. With the help of graphs, the effects of the various important parameters entering into the problem on the velocity, temperature, and concentration fields within the boundary layer are discussed. Also the effects of the pertinent parameters on the skin-friction coefficient and rates of heat and mass transfer in terms of the Nusselt number and Sherwood number are presented numerically in a tabular form. The results obtained show that the velocity, temperature, and concentration fields are appreciably influenced by the presence of chemical reaction, hall current, heat, and mass transfer. It is observed that the effect of Schmidt number and chemical reaction parameter is to decrease the velocity and concentration profiles in the boundary layer while the velocity profiles are increasing with increasing of hall parameter, Grashof numbers for heat and mass transfer. There is also considerable effect of hall current and chemical reaction on skin-friction coefficient and Nusselt number. In the present analysis various comparisons with previously published work are performed and the results are found to be in a good agreement.